Hierarchical graphene@MXene composite foam modified with flower-shaped FeS for efficient and broadband electromagnetic absorption. (10th January 2023) - Li, Shuangshuang; Tang, Xinwei; Zhao, Xu; Lu, Shijie; Luo, Jiangtao; Chai, Zheyuan; Ma, Tiantian; Lan, Qianqian; Ma, Piming; Dong, Weifu; Wang, Zicheng; Liu, Tianxi
Highlights: Ultralight magnetic composite foam with hierarchical structure is fabricated. Loading of MXene/FeS on rGO promotes the formation of hierarchical impedance in foam. Hierarchical impedance structure facilitates the entrance and dissipation of EMW. Optimization of impedance structure improves absorption capacity and bandwidth. Abstract: Developing high-performance broadband microwave absorption material becomes an urgent concern in the field of electromagnetic protection. In this work, an ultralight magnetic composite foam was constructed by electrostatic self-assembly of MXene on the surface of graphene skeletons, and subsequent hydrothermal anchoring of flower-shaped FeS clusters. Under the synergistic effect of MXene coating increasing conductive loss and FeS clusters improving magnetic loss, the rational construction of hierarchical impedance structure in foam can effectively promote the entrance and consumption of more incident electromagnetic waves. The minimum reflection loss (RLmin ) reaches –47.17 dB at a thickness of 4.78 mm, and the corresponding effective absorption bandwidth (EAB) is up to 6.15 GHz. More importantly, the microwave absorption performance of composite foam can be further optimized by controlling the loading of MXene and thermal treatment at a low temperature. The maximum of EAB for GMF-300 can be extended to an unprecedented value of 11.20 GHz (covering 6.10–17.30 GHz). Graphical abstract: Image, graphical abstract